THE SELECTIVE METHOD IN UNDERSTANDING, WRITING, AND PRONOUNCING ARABIC NUMERALS IN LEARNING THE ARABIC LANGUAGE AMONG SEVENTH-GRADE STUDENTS AT THE ISLAMIC UNITY SECONDARY SCHOOL IN SERANG - Humam Asyrofin; Moh Aman; Faedurrohman Faedurrohman; Nasrullah Nasrullah (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This study examines the effectiveness of the selective method in teaching Arabic numeral grammar, particularly in students' understanding of numeral texts' writing and pronunciation, among seventh-grade students at Al-Wahda Islamic Secondary School in Serang. The selective method integrates several teaching methods in proportion to learners' learning needs. The study used a qualitative approach, in addition to classroom procedural research, across the planning, implementation, observation, and evaluation stages in repeated courses. The results showed an apparent increase in students' comprehension, with the average score increasing from 68.33 to 76.42 in the first cycle and from 71.42 to 88.33 in the second cycle, and the normal gain (N-Gain) values improving from 0.28 to 0.61. These results show that the selective method effectively enhanced students' understanding of the rules of Arabic numerals.